Paradigmatic evidence of nationalism at Pesantren Ngruki - Moh In’ami,; Dwi Surya Atmaja,; Zahra Khusnul Lathifah,; Dahmany Chourouk, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The controversy surrounding Pesantren Ngruki inspired this study. This Pesantren was accused of being a terrorist den, making it difficult to defend itself. On this basis, an opportunity to refute any accusations was created by analyzing the pesantren through the lens of nationalism. This article explains how Pesantren Ngruki, one of Indonesia's Islamic educational institutions, approaches nationalism in social, political, and theological contexts. This study aims to thoroughly and comprehensively present Pesantren Ngruki's nationalism through an objective-critical approach that lends meaning to the reality of Pesantren's schooling while also addressing the specific practice of nationalism. This qualitative study aims to reveal evidence. The controversy surrounding Pesantren Ngruki inspired this study. This Pesantren was accused of being a terrorist den, making it difficult to defend itself. On this basis, an opportunity to refute any accusations was created by analyzing the pesantren through the lens of nationalism. This article explains how Pesantren Ngruki, one of Indonesia's Islamic educational institutions, approaches nationalism in social, political, and theological contexts. Another goal is to thoroughly and comprehensively present Pesantren Ngruki's nationalism through an objective-critical approach that lends meaning to the reality of Pesantren's schooling while also addressing the specific practice of nationalism. This qualitative study aims to reveal evidence.